The use of AI in cardiovascular research - Charles Benjamin Middleton (BioScientist: The Salford Biomedicine Society Magazine, 2024)
Cardiovascular research encompasses a vast array of challenges such as including the development of effective therapeutics and access to them, education about cardiovascular pathologies, and the implications of cost. But what if the problems we are trying to solve could be addressed with the use of artificial intelligence (AI)? This article explores how AI is currently being utilised in some medical fields and is continuously being improved for greater precision to aid in advancements in biological understanding4.